An experimental study on the combustion, performance and emission characteristics of a diesel engine fuelled with diesel-castor oil biodiesel blends. (April 2018) - Das, Mithun; Sarkar, Mouktik; Datta, Amitava; Santra, Apurba Kumar
Abstract: An experimental work has been performed to compare the combustion, performance and emission characteristics of a compression ignition engine running with diesel and three different blends of diesel and biodiesel (castor oil methyl ester, COME). The biodiesel has been prepared by alkaline transesterification using NaOH as catalyst. The properties of the fuels, like viscosity, surface tension, heating value, flash point and elemental composition, have been measured following standard test procedures. The variation of viscosity and surface tension of the pure fuels and their blends with temperature are experimentally determined. Experiments have also been performed on a porous sphere to compare the mass burning rate and transition velocity from envelope to wake flame for the pure fuels and their blends. The porous sphere experiment results indicate that diesel has higher evaporation rate than COME while the chemical reactivity of the latter is more than the former. The originality of the work is in using the fundamental information from the porous sphere experiments to explain the combustion characteristics in the engine cylinder. Studies in the engine reveal that combustion starts earlier with the diesel-biodiesel blends and the rate of pressure rise during the rapid combustion phase is also faster with the blended fuels compared to that with diesel. However, not much difference has been noticed in the performance (brake thermal efficiency, brake specific fuel consumption and exhaust gas temperature) and emission (CO, HC and NO) characteristics of the engine using the diesel fuel and diesel-biodiesel fuel blends. Graphical abstract: Highlights: Combustion, performance and emission characteristics of diesel and diesel-biodiesel blends are compared. Biodiesel prepared from castor oil through alkaline transesterification. Characterization of the fuels done through property evaluation. Combustion characteristics of fuels studied in porous sphere experiments.